TEST ANTINFLAMMATION CAPSULE COMBINATION OF MORINGA LEAVES (Moringa oleifera L) AND KARUK LEAVES (Piper sarmentosum Roxb. Ex. Hunter) EXTRACT TEST AGAINST MICE (Mus musculus) - Nia Kurniasih; Nurhidayati Harun; Ade Egie Prayogi (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2024)
Empirically utilized medicinal plants include Moringa leaves (Moringa oleifera L) and Karuk leaves (Piper sarmentosum Roxb. Ex. Hunter). Moringa leaves contain active compounds, such as vitamins, carotenoids, polyphenols, phenolic acids, flavonoids, alkaloids, glucosinolates, isothiocyanates, tannins, saponins, and oxalates. The leaves of karuk contain polyphenols, flavonoids, saponins, and tannins. This study aimed to assess the anti-inflammatory activity of combination capsules of Moringa and Karuk leaf extracts in mice (Mus musculus). Anti-inflammatory agents are drugs that can suppress or reduce inflammation. The aim of the experimental method used in this study was to determine the optimal concentration for anti-inflammatory activity. Carrageenan as an inflammatory mediator in mouse paws. The anti-inflammatory test involved five groups of animals, each consisting of five mice. The negative control group received Na-CMC, the positive control group was administered diclofenac sodium, and the test samples involved a combination capsule of Moringa and Karuk leaf extract at doses of 350, 700, and 1,050 mg. Measurements were performed every hour for 6 hours after carrageenan induction. Data analysis employed the One-way ANOVA method to ascertain whether variations in the dose of the combination capsule of Moringa and Karuk leaf extracts affected anti-inflammatory activity in mice. The results indicate that the greatest inflammation inhibition occurs with the 1,050 mg dose, resulting in 23% inhibition, followed by 22% at 700 mg and 13% at 350 mg. Statistical analysis yielded a p-value of 0.048, which was less than 0.05. This suggests a significant difference in the anti-inflammatory activity among the test groups ...